Body Image with Student Confidence of Muhammadiyah University of Sidoarjo: Citra Tubuh dengan Kepercayaan Diri Mahasiswa Universitas Muhammadiyah Sidoarjo - Wahyuningtyas, Reza Triana; Hazim, Hazim (Universitas Muhammadiyah Sidoarjo, 2023)
This research is motivated by the phenomenon of students who have moderate self-confidence, which is characterized by judgments from people around about their body image, resulting in the emergence of attitudes that lead to comparing themselves to others. This study aims to determine the relationship between body image and self-confidence of students at Muhammadiyah University of Sidoarjo. This study uses a quantitative research method with a correlational approach and uses a scale measuring instrument, namely the body image scale and the self-confidence scale. The sample in this study was 336 students from 9591 student population who were taken using incidental sampling technique, namely sampling based on chance or samples that were met or met by the researcher. Data analysis was performed using the Pearson product moment correlation using the SPSS 24 for windows. The results of data analysis show the correlation coefficient value of 0.632 with a significance of 0.000 <0.05, meaning that there is a positive and significant relationship between body image and self-confidence, the higher body image , the higher the student's self-confidence. On the other hand, the lower body image the student's self-confidence. The effective contribution of the body image variable is 40% to the self-confidence. While the remaining 60% is influenced by other factors.